Prognostic Significance of MicroRNA-375 Downregulation in Solid Tumors: A Meta-Analysis. (22nd October 2014) - Shao, Yingjie; Geng, Yiting; Gu, Wendong; Huang, Jin; Ning, Zhonghua; Pei, Honglei
Abstract : Objective . Recently, many studies have shown that microRNAs (miRNA) exhibit altered expression in various cancers and may play an important role as prognostic biomarker of cancers. We performed a meta-analysis to evaluate the impact of miR-375 expression in solid tumors on patients' overall survival (OS). Methods . Studies were identified by searching PubMed, Embace, and Cochrane Library (last search update was in May 2014) and were assessed by further quality evaluation. The pooled hazard ratios (HRs) with 95% confidence intervals (CIs) for total and stratified analyses were calculated to investigate the association between miR-375 expression and cancer patients OS. Results . Our analysis results indicated that downregulation of miR-375 predicted poor OS (HR = 1.91, 95% CI 1.48–2.45, P < 0.001 ). Subgroup analyses showed that lower expression of miR-375 was significantly related with poor OS in patients with esophageal carcinoma (HR = 2.24, 95% CI 1.69–2.96, P < 0.001 ) and non-small-cell lung cancer (NSCLC) (HR = 1.71, 95% CI 1.31–2.24, P < 0.001 ). Conclusions . The findings from this meta-analysis suggest that miR-375 expression is associated with OS of patients with malignant tumors and could be a useful clinical prognostic biomarker.